RESIKO PERAN EKONOMI IBU RUMAH TANGGA BAGI KELUARGA BATIH: Studi Kasus di Tulungagung Selatan tentang Efek Psikologis dan Sosial Profesi Sebagai Tenaga Kerja Wanita di Manca Negara - Nur Hadi (Jurnal Sejarah dan Budaya, 2013)
Abstract. There are two phenomena as focus of this research: (1) economic role of household wives as women labor at abroad, (2) the risks of its economic role for the left nuclear families. This research analyze relation of those phenomena for its psychological and social effects of the left nuclear families.This research uses qualitative approach and the kind of research is a case study. The research site is Besuki, one sub district of South Tulungagung region.This site is known as poor region and more one decade as a region that has many women labor at abroad. Results of this research are (1) the push factors in taking economic role as women labor are the limited income of previous occupation; influences of the economic success stories of women labor, wage of women labor higher than civil servant, and the result as women labor can be used for capital of many economic business; (2) The basic reason used to select women labor as their profession is based on calculation that more opportunity that can be reached than its risks, women labor prepare their preventive steps by following right and legal departure; (3) The economic effect is economic increasing at family and village level, the psychological effects are positive and negative impacts, and social effects are family conflicts, increasing number of divorce, and reducing amount of active women at village.